Financial System Stability in Indonesia during The Global Financial Crisis 2007/2008: Conventional vis-à-vis Islamic - Muh. Rudi Nugroho; Ibnu Qizam (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2014)
This research aims to analyze the financial stability especially in dual banking system in Indonesia and discusses the role of Islamic banks in the financial stability of national banks. In addition, this study also focuses on the analysis of the determinants of financial stability namely on the national banking Industry. This research uses panel data in which combined data between time series and cross section with an observation periods are 2005:1 - 2009:1 by using an internal variable of banks and macroeconomic data. Z-score analysis will be used as main tool analysis regressed with internal variable. Empirical results obtained from this research shows that during the period of 2005:1 - 2009:1 banking financial stability, for both conventional and Islamic and categorized based on an asset scale, the movement of the Z-score value is different. From the Z-score values analysis shows that Islamic banks are the most stable bank with a trend increased sharply when compared with other banks, namely conventional couterparts. If viewed from each category, small conventional banks more stable than small Islamic banks, and there are declining trend in 2005:1 to 2009:1. Whereas for large and middle conventional banks the trend of the Z-score movement are in the same patterns. This study also founds that the determinant of the banking stability can be seen from two sides namely bank's internal factors and macroeconomic factors. Internal factors consist of: Income Diversity (ID), Credit or Financing (Loan), Total Assets (TA), Operational Cost (Cost), Cost Income (CI), Loan Asset (LA), Current Liability (CL), Cash to Current Liabilities (CCL), Capital Bank (MDL). While macroeconomic factors consist of: inflation, BI Rate, Exchange Rate, Composite Index (JCI), the Gross Domestic Product (GDP). This research also examined the extent to which the role of Islamic banks and the global financial crisis to the financial stability of national banking. This analysis shows that the global financial crisis and Islamic banks affect significantly to the financial stability of banking industries in Indonesia.